BUDIDAYA RAJUNGAN DALAM KERAMBA JARING DITENGGELAMKAN SECARA TERPADU DI PERAIRAN KECAMATAN SIGERI KABUPATEN PANGKEP - Susan Yubelin De Fretes; Ihsan Ihsan; Hasrun Abdullah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
This study aims to (1) examine the physical and chemical aspects of marine oceanography, (2) determine the suitability of location and swimming crab culture techniques in submerged net cages, (3) find out the management strategies of crab culture management in submerged net cages. The results showed that the suitability of waters for crab cultivation activities in the karamba nets was submerged by using indicators of temperature, salinity, oxygen, pH and brightness obtained two suitability criteria, namely sesai and not. The results of the suitability analysis of crab cultivation land using a Geographic Information System (GIS) obtained two criteria for suitability of cultivated land with an area of each appropriate category that is 46,785.32 ha and not according to 1,152.4 ha. The results of management strategies that can be applied to realize integrated management of small crab culture include: 1) Development and socialization of small crab culture; 2) Management of integrated small crab cultivation; 3) Law enforcement related to the destruction of coastal ecosystems 4) Prohibition of capturing crabs laying eggs; 5) Construction of small crab hatcheries for small crab cultivation needs; 6) Development and provision of venture capital.